Classroom Management, Record Keeping, And Student Academic Performance in Public Senior Secondary Schools in Obio/Akpor Local Government, Rivers State - Kelechi C, Ibe-Moses; O, Dike, Ebubechukwum; Monilola, Binuyo; Racheal, Dada (Journal of Posthumanism, 2026)
Classroom management and record keeping are crucial contributors to academic performance. There has been loud outcry by parents over their wards performance and the need to follow up with their academic performance.This is largely because academic records are not properly kept, where it is kept, it is not readily available to parents as at when need. The ongoing deterioration in academic performance prompts this research. The population for this study consists of students and teachers from public senior secondary schools, Obio-akpor Local Government Area (LGA), Rivers State, Nigeria.The total population for public senior secondary school students in Obio-akpor local government of rivers state is 15,530, with a total of 21 senior public schools and 1,297 teachers.Inferential statisticsofmultiple regression analysis was used to test the research hypotheses.The study found that effective classroom management plays a significant role in enhancing student academic performance. Also, there is a strong relationship between classroom management, record-keeping, and student academic performance.The research revealed that effective classroom management practices, including organization, reinforcement, and instructional monitoring, significantly correlate with improved student academic performance. The study recommended that there should be Implementation of Digital Record-Keeping Systems: Schools should transition from manual to digital record-keeping systems to enhance accuracy and efficiency in tracking student progress among others.